Hospital food service quality improvement questionnaire (HFSQIQ) : development, translation and validation of questionnaire - Osman, Noor Suzana; Md Nor, Norazmir; Mustafa, Norashikin; Rusali, Roszanadia; Ishak, Ruzaina (Faculty of Medicine, Universiti Malaya, 2023)
The hospital food service department provides meals to staff, patients, and their caregivers while adhering to dietary therapy guidelines and promoting nutritional wellness. High-quality food service plays a pivotal role in offering inpatients nourishing meals that promote physical and mental well-being, aiding their recovery and overall health during their hospitalisation. This study aimed to develop and validate a tool for measuring and evaluating hospital food operations using the Total Quality Management approach. A literature review, in-depth interviews with food service employees, and a peer-review process were conducted to identify the domains and items for the questionnaire. A “Hospital Food Service Quality Improvement Questionnaire” (HFSQIQ) with 61 items in six domains was developed and the content validation was performed by seven experts. The questionnaire was translated into Malay, and the internal consistency of the HFSQIQ was examined using Cronbach’s alpha. Resultantly, the HFSQIQ depicted high validity and reliability, with a high I-CVI and Kappa index rating for most items and a Cronbach alpha value of 0.97 and 0.98 for the importance and performance scales, respectively. In conclusion, the HFSQIQ is a useful tool for evaluating and improving the quality of hospital food service operations.